Towards a Contextualized Understanding of Scholarly Impact: The Development and Implications of the Contextualized Scholarly Impact Index (CSII) - Grace Yulianti; Mohammad Chaidir; Dadang Irawan (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores the development and implications of the Contextualized Scholarly Impact Index (CSII), a framework designed to address the limitations of traditional metrics in assessing scholarly contributions. The review highlights the need for a more nuanced understanding of scholarly impact that incorporates contextual factors, such as collaboration, societal relevance, and interdisciplinary engagement. Through a comprehensive analysis of existing literature, the review identifies key themes that underscore the importance of recognizing diverse forms of scholarship, including public engagement and community involvement. The findings indicate that the CSII has the potential to transform the landscape of scholarly impact assessment by promoting a holistic and equitable evaluation framework. This shift aligns with the growing consensus within the academic community for more inclusive methodologies that reflect the multifaceted nature of research contributions. However, the review also acknowledges limitations, including the subjective interpretation of literature, the rapidly evolving nature of the field, and the need for empirical validation of the CSII. Ultimately, this review lays the groundwork for future research and practice, advocating for a contextualized approach that enriches our understanding of scholarly impact in contemporary academia.